La agresividad infantil y su incidencia en el desarrollo cognitivo cognitivo en los niños y niñas del centro de Eduación Inicial las Ardillitas del cantón Machala, periodo lectivo 2012-2013. - Sánchez Brito, Norma Elizabeth (2013)
Childhood aggression is one of the main complaints from parents and teachers about the children giving them around frequently. We often face aggressive, manipulative or rebellious children but not really know what to do with them or how we can influence their behavior to achieve change.